2019
DOI: 10.1016/j.landurbplan.2018.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic influences on the time budgets of urban vervet monkeys

Abstract: Continuing urban developments are ecologically changing many landscapes. A greater understanding of how wildlife adapt behaviorally to these changes is necessary to inform management decisions. Time is a valuable resource to wildlife and a reflection of ecological pressures on the behavioral repertoire of an animal. Data on urban vervet monkey, Chlorocebus pygerythrus, time budgets are generally limited and dated. We aimed to investigate the effect of anthropogenic influences, both human food consumption (posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
5
29
0
Order By: Relevance
“…Interestingly, some urban-dwelling populations have been shown to spend more time resting and engaging in social activities compared to less urban groups (Saj et al, 1999;El Alami et al, 2012;Jaman & Huffman, 2013;Koirala et al, 2017;Ilham et al, 2018;Thatcher et al, 2019). This suggests a potentially positive effect (rather than negative) of anthropogenic factors on animals' time budgets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some urban-dwelling populations have been shown to spend more time resting and engaging in social activities compared to less urban groups (Saj et al, 1999;El Alami et al, 2012;Jaman & Huffman, 2013;Koirala et al, 2017;Ilham et al, 2018;Thatcher et al, 2019). This suggests a potentially positive effect (rather than negative) of anthropogenic factors on animals' time budgets.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in areas degraded by human activities, animals might be forced to increase their travel time, thereby decreasing their resting and social time, either in order to avoid humans or because natural food sources become scarce (red deer, Cervus elaphus: Grover & Thompson, 1986;lion-tailed macaque, Macaca silenus: Menon & Poirier, 1996;tonkean macaque, Macaca tonkeana: Riley, 2007). In contrast, other studies reveal that animals that live and thrive in an anthropogenic environment tend to spend more time resting and socializing than groups living in less anthropogenic areas (e.g., vervet monkey, Chlorocebus pygerythrus: Saj et al, 1999;Thatcher et al, 2019;Barbary macaque: El Alami et al, 2012;rhesus macaque: Jaman & Huffman, 2013; assamese macaque, Macaca assamensis: Koirala et al, 2017;long-tailed macaque: Ilham et al, 2018). Such beneficial effects may be due to reliance on anthropogenic foods that tends to be higher in calories, more abundant, and more digestible than natural foods (Forthman-Quick, 1988;Rode et al, 2006;Riley et al, 2013;McLennan & Ganzhorn, 2017), and researchers argue that in this condition animals can spend less time feeding, and consequently increase their time spent resting and/or socializing (Jaman & Huffman, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…If primates are constantly exposed to, and/or prefer consuming human food to natural food, individuals may spend more time foraging on anthropogenic food relative to natural food. Previous studies on primate populations that thrive in anthropogenic landscapes have revealed that such animals also spend more time resting and socializing than populations in less perturbed landscapes, likely due to the high caloric value of anthropogenic foods leading to less time spent consuming or in search of natural food (El Alami, Lavieren, Rachida, & Chait, ; Hockings, Anderson, & Matsuzawa, ; Jaman & Huffman, ; Koirala et al, ; Saj et al, ; Thatcher, Downs, & Koyama, ). By the logic of this free‐time hypothesis, individuals that forage more on anthropogenic food may also have more time (rather than less time, as in time‐constraints) or energy to invest in grooming and/or other affiliative interactions (Kaburu, Beisner, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We obtained repeated, reliable counts from five vervet monkey troops, with a mean troop size of 31.6 (±8.84 SD ) (Table ). All troops had access to permanent water sources; however, two troops had relatively more access to non‐natural foods than others (Thatcher, Downs, & Koyama, ). These two troops had significantly larger troop sizes than troops more reliant on natural food sources.…”
Section: Resultsmentioning
confidence: 99%
“…Research on primate behavioural flexibility in anthropogenic habitats has increased markedly since the 2000s; however, this only includes 17% of currently recognised species (McLennan, Spagnoletti, & Hockings, ). Therefore, while vervet monkeys are shown to persist in urban areas (Chapman & Fedigan, ; Horrocks & Baulu, ; McLennan et al, ; Patterson, Kalle, & Downs, , ,; Shimada & Shotake, ; Thatcher, Downs, & Koyama, , ; Wolfheim, ), the absence of urban spatial data has greatly curtailed the efficacy of vervet monkey management efforts in transformed landscapes like KZN. To date, most management decisions have been based on previous practices, public opinion and the suggestions of researchers both with and without relevant experience and knowledge of the local vervet monkey population (Simbithi Environmental Group, 2016 pers.…”
Section: Introductionmentioning
confidence: 99%